Assessment of GFRP bond behaviour for the design of sustainable reinforced seawater concrete structures - Soares, Sérgio (2020)
Freshwater is an increasingly scarce resource. Its use in the production of concrete is one important contributor to its fast depletion. Alternatively, the use of seawater for reinforced concrete production, combined with the use of glass fibre reinforced polymers (GFRP) as reinforcement, may represent an interesting solution to increase concrete sustainability. The objective of this paper is to explore this promising solution through the development of concrete compositions with seawater. Additionally, it is also an objective to assess the bond behaviour between GFRP rods and concrete, in a design perspective. The influence of concrete age, rod diameter and anchorage length were also investigated. An analytical model capable of determining the local bond stress-slip laws was used. Results demonstrated that the use of seawater had no relevant effects on neither concrete mechanical properties nor bond behaviour.